Science with reason (Hodder and Stoughton, 1995)
This book consists four sections. Section A introduces some of the main ideas of the book; Section B has three chapiters that fucus particularly on the different classroom strategies that teachers can use to encourage their children to talk and question what they do; Section C is a wide variety of stories, arranged roundly by age, starting with the yougest; Section D is chapiters that pull together some of the themes from the stories in section C